Analysis of Literacy and Numeracy Skills in Enhancing Garment Production Competencies Among Fashion Technology Vocational Training Students - Endang Widyastuti; Amin Yusuf; Decky Avrilianda; Arini Dwi Cahyani (Edutech Publishing Media, 2026)
The growing demand for skilled workers in Indonesia’s textile and garment industry highlights the importance of foundational competencies in vocational training. This study explored the role of literacy and numeracy skills in supporting garment production competencies among trainees in the Fashion Technology program at Balai Besar Pelatihan Vokasi dan Produktivitas Semarang. A qualitative approach was employed involving 15 trainees who completed literacy, numeracy, and competency assessments, supported by semi-structured interviews with three trainees representing different ability levels and two instructors. Assessment results showed that 53% of trainees demonstrated high literacy skills, 47% showed high numeracy skills, and 53% achieved high garment production competency. Interview findings indicated that literacy skills supported trainees’ ability to understand technical terminology, interpret work instructions, and follow production procedures, while numeracy skills facilitated accurate measurements, calculations, and technical decision-making. The findings suggest that literacy and numeracy function as important enabling factors in competency development. This study contributes to vocational education literature by providing empirical evidence on how foundational skills are embedded in nonformal fashion training and support workforce preparation in the garment industry.